The Value of Heroicity in The Folk Sianak Gold Tales of Radin Jambat by Yuliadi M.R. d - Ningsih, Iraliya; Sumarti, Sumarti; Suyanto, Edi; Samhati, Siti; Munaris, Munaris (UNDIKMA, 2024)
Heroic values can be used as an example for humans reflected in the characters contained in folklore. Overall, the heroic value in the story has a strong appeal and provides many benefits for the reader or audience. This study aims to describe the heroic value contained in the folklore of The Golden Child of Radin Jambat by Yuliadi M.R. using media technology The data in this study are in the form of quotations or conversations obtained from the folklore of The Golden Child of Radin Jambat by Yuliadi M.R. This study uses a qualitative descriptive approach. The results showed the existence of heroic values in the folklore of The Golden Child of Radin Jambat by Yuliadi M.R in the form of courage, loyalty, and self-sacrifice